(untitled) (Vietnam Journal of Community Medicine, 2024)
Aim: Evaluation of the value of CT-scanner to diagnose acute pancreatitis with fluid collection. Objects and methods: Study of 181 acute pancreatitis with fluid collection treated by ultrasound – guided percutaneous catheter drainage at Military Hospital 103 from January 2021 to May 2023. The patient undergone multiple detector scan of abdomen with contrast in the first day. The examination, diagnosis, and treatment according to the guidelines of the World Society of Emergency Surgery (WSES) 2019. Results: CT-Scanner with contrast agent, Balthazar grade E was the most (56.9%), followed by grade D and C (28.7% and 13.8%), there was 1 case of grade B. Correct diagnosis of acute necrotizing pancreatitis was 98.1%, sensitivity was 82.1%, specificity was 96.5%, positive predictive value was 98.1%, negative predictive value was 71.8% and Kappa index was 0.73. Clinically appropriate CTSI index was 71.8%, of which 94.1% was suitable for mild level, 65.3% for moderate level and 56.3% for severe level. Conclusions: CT-Scanner with contrast agent to diagnose acute necrotizing pancreatitis has high sensitivity and specificity, however, the accuracy rate of using CTSI indext to reflex the disease condition was low. Therefore, patient should be taken CT-Scanner again after 72 hours of admission for a more accurate diagnosis.